Elemental sulfur-based autotrophic denitrification and denitritation: microbially catalyzed sulfur hydrolysis and nitrogen conversions. (1st April 2018) - Kostrytsia, Anastasiia; Papirio, Stefano; Frunzo, Luigi; Mattei, Maria Rosaria; Porca, Estefanía; Collins, Gavin; Lens, Piet N.L.; Esposito, Giovanni
Abstract: The hydrolysis of elemental sulfur (S 0 ) coupled to S 0 -based denitrification and denitritation was investigated in batch bioassays by microbiological and modeling approaches. In the denitrification experiments, the highest obtained NO3 − -N removal rate was 20.9 mg/l·d. In the experiments with the biomass enriched on NO2 −, a NO2 − -N removal rate of 10.7 mg/l·d was achieved even at a NO2 − -N concentration as high as 240 mg/l. The Helicobacteraceae family was only observed in the biofilm attached onto the chemically-synthesized S 0 particles with a relative abundance up to 37.1%, suggesting it was the hydrolytic biomass capable of S 0 solubilization in the novel surface-based model. S 0 -driven denitrification was modeled as a two-step process in order to explicitly account for the sequential reduction of NO3 − to NO2 − and then to N2 by denitrifying bacteria. Graphical abstract: Image 1 Highlights: The use of elemental S 0 resulted in a denitrification rate of 20.9 mg NO3 − -N/l·d. Enriched biomass could tolerate a nitrite concentration as high as 240 mg NO2 − -N/l. S 0 hydrolysis was performed in the biofilm by Helicobacteraceae species. The model coupled biological surface-based S 0 hydrolysis to denitrification. Numerical simulations demonstrated model consistency with experimental data.